2019
DOI: 10.1111/1744-7917.12676
|View full text |Cite
|
Sign up to set email alerts
|

Australian sugarcane soldier fly's salivary gland transcriptome in response to starvation and feeding on sugarcane crops

Abstract: The soldier fly is an endemic pest of sugarcane in Australia. Small numbers of larvae can cause significant damage to roots and reduce the crop yields. Little is known about the composition and function of the soldier fly salivary gland, its secretions, and their roles in insect-plant interactions. In this study, we performed transcriptome analysis of the salivary glands of starved and sugarcane root-fed soldier fly larvae. A total of 31 119 highly expressed assembled contigs were identified in the salivary gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Further work could also utilize tissue-specific gene expression to determine, where gene expression changes are most prominent. For example, larvae of the soldier fly, Inopus falvus (Diptera: Stratiomyidae), differentially express numerous genes in the salivary glands in response to starvation stress (Etebari et al 2020). Other tissues of interest may be different sections of the gut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work could also utilize tissue-specific gene expression to determine, where gene expression changes are most prominent. For example, larvae of the soldier fly, Inopus falvus (Diptera: Stratiomyidae), differentially express numerous genes in the salivary glands in response to starvation stress (Etebari et al 2020). Other tissues of interest may be different sections of the gut.…”
Section: Discussionmentioning
confidence: 99%
“…attaining a minimum size by prolonging the larval development) (Hector and Nakagawa 2012). Moreover, starvation leads to substantial shifts in gene expression within individuals (Moskalev et al 2015; Jiang et al 2019; Etebari et al 2020; Farahani et al 2020). However, little is known how long these effects may persist (McCue et al 2017) and to which extent parental starvation may affect gene expression of offspring experiencing starvation.…”
Section: Introductionmentioning
confidence: 99%
“…Serinetype endopeptidases have been earlier identified from the transcriptome and proteomes of H. halys, and were demonstrated to function as extra-oral digestive enzymes (Liu & Bonning, 2019;Lomate & Bonning, 2016;Peiffer & Felton, 2014), which appeared to be a prevalent feeding strategy among herbivorous hemipterans (Wright, et al 2006;Lomate & Bonning, 2016;Zhu et al, 2016). In contrast, identification of ankyrin proteins from the salivary glands/saliva of herbivorous insects was scarcely reported, except in the white-backed planthopper (Sogatella furcifera) (Miao et al, 2018), and the yellow soldier fly (Inopus flavus) (Etebari et al, 2020), with unknown functions. Serving as linkers to mediate the protein-protein interactions, ankyrin repeats play essential roles in a myriad of physiological processes in pro-and eukaryotes, including transcription and cell cycle regulation, signal transduction, and stress responses (Li et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In case of date palm tree, there are a few previous studies [23][24][25][26] explaining the physiology and genomics, however, very few studies have also shown the differential gene expression of date palm during abiotic stress conditions 27 . There are recent studies performed to understand the infestation process and related gene's regulation in aphid feedings to susceptible plants 28 , Ostinia furnacalis leaf feeding to maize 29,30 , soldier fly on sugarcanes in Australia, aphid attacks on wheat crops, and Lepidoptera species infection to cotton 31,32 . These studies have used detailed RNA-Seq based method to point out various underlying mechanisms during herbivory infection.…”
mentioning
confidence: 99%